MANAGEMENT OF PULMONARY TUBERCULOSIS PATIENT WITH THEIR CULTURE CONVERSION STATUS IN KENDARI CITY, PROVINCE OF SULAWESI TENGGARA, INDONESIA - Saputra, Hermawan; Asyary, Al; Madjid, Ruslan; Salam, Asrun (Journal of Ultimate Public Health, 2017)
Background: Tuberculosis (TB) conversion is a vital milestone that remains rarely assessed in TB mitigation programs. Objectives: This study aimed to explain the effects of body mass index (BMI) and housing index status on TB conversion in a developing country. Methods: A cross-sectional study was conducted on 51 TB patients in the three health centres (Puskesmas) with the highest TB incidences in Kendari City, Southeast Sulawesi, Indonesia, using data reported in the the first quarterly report of 2008. We used bivariate association with Fisher’s exact test to review TB conversion determinants. Results: The results indicated that TB occurred predominantly in men (51%) and people over 40 years old (74,5%). Factors indicating that TB conversion is associated with both adequate nutrition and housing in TB patients approached significance (RP = 1.0 and p = 0.05). Conclusions: However, housing and nutrition status are rarely considered as determinants of TB conversion in the assessment of TB outcomes. We suggest increasing sample distribution and introducing other factors related to healthcare as supply variables for further study.